Digital archives and recombinant historical geographies. (December 2022) - Hodder, Jake; Beckingham, David
This article considers how digitisation is reshaping archival research in geography. Digitisation is more than a technical convenience, something that simply speeds up existing ways of working. Through novel practices of recombination, digital archive platforms enable researchers to extract and recombine fragments of historical information, drawn across multiple periods, places, collections and contexts. This represents a fundamental change in how we research the past. In this paper, we conceptualise recombination as an uneven geographical phenomenon, we situate it within the shifting political and economic infrastructures of archives, and pose a series of ethical questions for geographers to consider.